The Commodity Structure of World Trade: Comment - Spiegelglas, Stephen (Quarterly Journal of Economics, 1961)
Journal Article The Commodity Structure of World Trade: Comment Get access Stephen Spiegelglas Stephen Spiegelglas Boston University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 1, February 1961, Pages 157–165, https://doi.org/10.2307/1883213 Published: 01 February 1961